Changes in the relationship between attachment and emotion recognition from adolescence to adulthood - Katalin Oláh (PLoS ONE, 2025)
The present study investigated the relationship between attachment and emotion recognition in adolescents and adults. While previous research has found an association between these constructs in young children, as of yet, only a handful of studies have extended the investigation to later periods of life, either focusing on adults or adolescents. To capture the developmental changes that may take place during the transition from childhood to adulthood, we present findings with the same methodology on a group of adults and adolescents between the ages of 14 and 18. Participants completed the Reading the Mind in the Eyes test and filled out a self-report questionnaire on attachment style. Results suggest that attachment avoidance is associated with poorer emotion recognition capacities in adolescents, specifically in the case of positive emotions, while anxiety may have a positive, although weaker effect on mindreading. These associations are attenuated significantly by adulthood. Results are discussed in terms of information processing biases associated with attachment anxiety and avoidance.